THE COMMON ERRORS IN THE LEARNING OF THE SIMULTANEOUS EQUATIONS - Pg. Mohammad Adib Ridaddudin Pg. Johari; Masitah Shahrill (IKIP Siliwangi and I-MES, 2020)
The purpose of this study is to understand the causes of common errors and misconceptions in the learning attainment of simultaneous equations, specifically on linear and non-linear equations with two unknowns. The participants consisted of 30 Year 9 students in one of the elite government schools in Brunei Darussalam. Further analyses of their work led to the categorisation of four factors derived from the recurring patterns and occurrences. These four factors are complicating the subject, wrong substitution of the subject, mathematical error and irrational error in solving the question. These factors usually cause participants to make errors or simply misconceptions that usually led them to errors in solving simultaneous equations.